2023
DOI: 10.1523/jneurosci.2004-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Transcutaneous Vagus Nerve Stimulation Specifically Enhances Working Memory Gate Closing Mechanism: A System Neurophysiological Study

Abstract: Everyday tasks and goal-directed behavior involve the maintenance and continuous updating of information in working memory (WM). WM gating reflects switches between these two core states. Neurobiological considerations suggest that the catecholaminergic and the GABAergic are likely involved in these dynamics. Both of these neurotransmitter systems likely underly the effects to auricular transcutaneous vagus nerve stimulation (atVNS). We examine the effects of atVNS on WM gating dynamics and their underlying ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…On a behavioral level, participants committed fewer errors and showed longer RTs in gate closing than opening, replicating previous research. 7 , 8 , 9 , 10 , 11 As mentioned earlier, gate closing and opening represent switch costs from a reference to a comparison trial and vice versa. The DDM of the behavioral data provided further insights into the computational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a behavioral level, participants committed fewer errors and showed longer RTs in gate closing than opening, replicating previous research. 7 , 8 , 9 , 10 , 11 As mentioned earlier, gate closing and opening represent switch costs from a reference to a comparison trial and vice versa. The DDM of the behavioral data provided further insights into the computational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, data from two previous experimental studies 7 , 12 in healthy individuals of european ancestry were aggregated ( N = 63 in total; 20 males, mean age 25.1 ± 4.6 years, all right-handers). All participants had normal or corrected to normal vision, normal hearing, and no history of neurological or mental illnesses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although imaging studies elucidating tVNS effects on AD are in the preliminary stages, some hypotheses have been formulated based on existing research. A randomized crossover trial involving a healthy population found that taVNS influenced working memory by modulating the alpha band activity of the EGCs, potentially mediated by the GABA system ( Konjusha et al, 2023 ). Huang et al (2023) conducted a clinical study using fMRI and observed that repetitive taVNS could modulate functional connectivity within the CNS region of the vagal pathway and limbic system, including the bilateral hippocampus, postcentral gyrus, thalamus, and basal ganglia.…”
Section: Vns Can Re-orchestrate Brain Plasticity Optimally In Admentioning
confidence: 99%
“…However, the external ear is also innervated by trigeminal nerve fibers, partially overlapping with the vagus territory [ 100 , 101 ]; therefore, an appropriate electrode positioning easily results in the stimulation of both trigeminal and vagal afferents [ 6 , 102 ]. The study of auricular tVNS has seen great development in recent years, especially with regard to improved cognitive performance, not only in the clinical population but also in healthy subjects [ 103 , 104 , 105 , 106 , 107 ]. While the neurobiological mechanisms are still unclear, the available literature mostly seek to explain the positive effects of tVNS on cognitive performance in terms of a change in brain NE levels [ 64 , 108 ].…”
Section: New Possibilitiesmentioning
confidence: 99%